Medicinal plant use by the Tujia people in northeastern Guizhou, China: an ethnobotanical study - Xie, Jian; Wang, Pan; Jiang, Qin; Chen, Qiuyi; Xiao, Min; He, Wanke; Nie, Xuqiang; Liu, Sha; Zhao, Yongxia; Zheng, Guisen; Bai, Zhixun; Li, Shuo; et al. (Frontiers in Pharmacology, 2025)
IntroductionThis study focuses on the traditional medical knowledge of the Tujia ethnic minority in Guizhou, particularly the use of traditional herbs with potential for development. The research documents and aims to protect this knowledge, which is vital for preserving the cultural heritage and enhancing the medicinal resources of the Tujia people.MethodsThis study was conducted in the Tongren region of eastern Guizhou, the primary settlement area of the Tujia people. We used ethnobotanical and ethnoecological research methods, including field surveys, interviews with local herbal doctors, and documentation of medicinal plant species.ResultsA total of 168 traditional Tujia medicinal plants from 70 families were recorded. The most represented families included Liliaceae (12 species), Crassulaceae (9 species), Asteraceae (9 species), Orchidaceae (9 species), Rosaceae (7 species), and Apiaceae (7 species). Among these, the three most frequently recorded medicinal plant species by our 124 informants were Artemisia lavandulifolia Salisb., Pyracantha (L.) Voss, and Urtica japonica Thunb. These plants are primarily used to treat injuries, insect and snake bites, rheumatic pain, and gastrointestinal diseases, reflecting the local climate and ecological conditions. We identified seven primary herbs that are also traditional wild edible plants crucial to the Tujia people’s daily lives. However, issues such as the aging of traditional Tujia herbal doctors, lack of successors, and unsystematic and unsafe medicinal practices were also identified.ConclusionThe findings provide essential information for preserving the traditional cultures and developing the medicinal resources of the Tujia people. There is a need for systematic documentation and training to ensure the transmission of traditional knowledge to future generations. Future research should focus on the in-depth study and development of the valuable herbs identified in this study, aiming to integrate traditional knowledge with modern scientific approaches for better healthcare solutions.